Russian Language in the Space of Culturein the Former USSR Countries - Svetlana Yu. Kamysheva; Albina A. Filippova (Polylinguality and Transcultural Practices)
The humanitarian policy of the Russian Federation prescribes active promotion of the principle of multilingualism in the activities of international universal and regional organizations, including the preservation and expansion of the use of the Russian language. For three years, the Centre for Language Policy and International Education of the Pushkin Institute of Russian Language has been conducting a scientific experiment under copyright, which is complex research aimed at determining the rating of the Russian language in countries near and far. In 2023, the third edition of “The Index of the Position of the Russian Language in the World,” dedicated to the Year of the Russian Language in the CIS, was published. It not only collects and analyses relevant data compared to the previous years, 2020 and 2022, but also introduces new parameters for assessing the position of the Russian language abroad. Among the latter, there is the parameter “Russian language in the space of cultureˮ, designed to reflect the degree of activity of the Russian language in the post-Soviet space in such social institutions as libraries, museums, and theatres, trace the integration processes in the humanitarian sphere in the countries of the former USSR, determine the systems of interaction in these areas of humanitarian knowledge. The demand for the theme of this project overall has been repeatedly confirmed by state and public organizations in Russia and other countries around the world.